The Use of the Minimally Coached Role-Playing Client in Training Evaluation - Friesen, Deloss D.; Dunning, G. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study describes the use of minimally trained role-playing clients in thee valuation of a counselor-training course. Two such role-playing clients were briefly instructed in a separate role and given a list of 15 or 16 variable which were present to each trainee. The results indicated that with minimal coaching a role-playing client could accurately and reliably play the role. This role stability allows students to be comparatively assessed in a life-like situation. The study concludes that with minimal coaching, the role-playing clients could be used effectively in the evaluation of training programs.